2013
DOI: 10.3382/ps.2012-02845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saccharomyces boulardii and Bacillus subtilis B10 on intestinal ultrastructure modulation and mucosal immunity development mechanism in broiler chickens

Abstract: The recent ban on the use of antibiotics as a feed additive has led to the search for alternative sources of antibiotics in the feed industry. Presently, probiotics are considered as a potential substitute for antibiotic as a live biotherapeutic agent to improve animal health and performance. Accordingly, study was focused on evaluating the effect of Saccharomyces boulardii (Sb) and Bacillus subtilis B10 (Bs) on ultrastructure modulation and mucosal immunity development in broiler chickens. A total of three hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 24 publications
7
101
1
12
Order By: Relevance
“…Individual strategies examined included direct-fed microbial (probiotics) and live microbial feed supplements which beneficially affect the host animal by improving its intestinal balance (Rajput et al, 2013; Salim et al, 2013); prebiotics, indigestible feed ingredients that beneficially affect the host by selectively stimulating the activity of beneficial bacteria resident in the animal tract (Patterson and Burkholder, 2003; Baurhoo et al, 2009; Samanta et al, 2013); vaccination (Desin et al, 2013) and immune-stimulation through cationic peptides and cytokines (Asif et al, 2004; Kogut et al, 2013); bacteriocins and antimicrobial peptides (Joerger, 2003; Svetoch and Stern, 2010); bacteriophages (Huff et al, 2005, 2013; Zhang et al, 2013); organic acids with antimicrobial activities; herbs, spices and other plant extracts (González-Lamothe et al, 2009); and controlled organic productions with emphasis on diet formulation and ingredient selection, cereal type and dietary protein source and level (Drew et al, 2004; O'Bryan et al, 2008). To date, none of these strategies have been systematically implemented.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…Individual strategies examined included direct-fed microbial (probiotics) and live microbial feed supplements which beneficially affect the host animal by improving its intestinal balance (Rajput et al, 2013; Salim et al, 2013); prebiotics, indigestible feed ingredients that beneficially affect the host by selectively stimulating the activity of beneficial bacteria resident in the animal tract (Patterson and Burkholder, 2003; Baurhoo et al, 2009; Samanta et al, 2013); vaccination (Desin et al, 2013) and immune-stimulation through cationic peptides and cytokines (Asif et al, 2004; Kogut et al, 2013); bacteriocins and antimicrobial peptides (Joerger, 2003; Svetoch and Stern, 2010); bacteriophages (Huff et al, 2005, 2013; Zhang et al, 2013); organic acids with antimicrobial activities; herbs, spices and other plant extracts (González-Lamothe et al, 2009); and controlled organic productions with emphasis on diet formulation and ingredient selection, cereal type and dietary protein source and level (Drew et al, 2004; O'Bryan et al, 2008). To date, none of these strategies have been systematically implemented.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…Innate immunity is a first-line defense against pathogen colonization, and recent findings confirmed that dietary B. subtilis can modulate immune response in broiler chickens (Lee et al, 2010). Another recent study showed that Bacillus -based DFM significantly induced inflammatory and anti-inflammatory cytokines in the jejunum and ileum of broiler chickens (Rajput et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…this was also reported by ALUWONG et al (2013), who showed that nutrition plays a vital role in maintaining the pro-oxidant-antioxidant balance. Moreover, CaPCarOVa et al (2010) and RAJPUT et al, (2013) noticed that some microorganisms could help in oxidation resistance, scavenge hydroxyl radicals and increase antioxidant capacity. thus, the increased activity of all these antioxidant enzymes in the present study may be attributed to the environmental pathogens of Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%